Anti-miR-223-5p Ameliorates Ischemic Damage and Improves Neurological Function by Preventing NCKX2 Downregulation after Ischemia in Rats - Ornella Cuomo; Pasquale Cepparulo; Serenella Anzilotti; Angelo Serani; Rossana Sirabella; Paola Brancaccio; Natascia Guida; Valeria Valsecchi; Antonio Vinciguerra; Pasquale Molinaro; Luigi Formisano; Lucio Annunziato; et al. (Elsevier, 2019)
It has been demonstrated that the K+-dependent Na+/Ca2+ exchanger, NCKX2, is a new promising stroke neuroprotective target. However, because no pharmacological activator of NCKX2 is still available, microRNA (miRNA) may represent an alternative method to modulate NCKX2 expression. In particular, by bioinformatics analysis, miR-223-5p emerged as a possible modulator of NCKX2 expression. In the light of these premises, the aims of the present study were: (1) to evaluate miR-223-5p and NCKX2 expression in the temporoparietal cortex and striatum of rats subjected to transient middle cerebral artery occlusion; (2) to evaluate whether miR-223-5p targets the 3' UTR of the NCKX2 transcript; and (3) to evaluate the effect of miR-223-5p modulation on brain ischemic volume and neurological deficits. Our results showed that miR-223-5p expression increased in a time-dependent manner in the striatum of ischemic rats in parallel with NCKX2 downregulation, and that the transfection of cortical neurons with miR-223-5p induced a reduction of NCKX2 expression. Moreover, a luciferase assay showed that miR-223-5p specifically interacts with the NCKX2 3' UTR subregion (+7037 to +8697), thus repressing NCKX2 translation. More interestingly, intracerebroventricular infusion of anti-miR-223-5p prevented NCKX2 downregulation after ischemia, thus promoting neuroprotection. The present findings support the idea that blocking miR-223-5p by antimiRNA is a reasonable strategy to reduce the neurodetrimental effect induced by NCKX2 downregulation during brain ischemia.